The use of the mobile phone in the rural zones of Peru - Franciskovic, Jubitza Mariana; Miralles, Francesc (Universidad ESAN. ESAN Ediciones, 2021)
Purpose. The main objective of the research is to examine whether the possession and the consumption of the service of a mobile telephone by the families of rural zones has improved their wellbeing in the last 10 years (2007–2016). Design/methodology/approach. A quantitative analysis of panel data is proposed in order to analyze the effect of the use of the mobile telephone in rural zones by region of Peru during the last 10 years and capture the unobservable heterogeneity during the said period. In this manner, it is hoped to investigate the effect of the increased use of said technology in Peru. Findings. The results obtained show that the increase in the acquisitions of mobile telephones in rural zones has had a positive impact on the wellbeing of households. Continuous business innovation driven by citizens’ needs and the greater accessibility of mobile telephones are the main reasons based on the Peruvian context under study. Originality/value. In Peru, there has been an explosive increase in users of mobile telephones in the last 10 years. The use of this technology may be arriving in rural households before other basic services, provoking individual and social changes and creating new employment and income opportunities. This would support the recent recognition of the mobile telephone as an essential tool for development, especially in underdeveloped countries.

Propósito: El objetivo principal de la investigación es examinar si la posesión y el consumo del servicio de telefonía móvil por parte de las familias de zonas rurales ha mejorado su bienestar en los últimos 10 años (2007-2016). Diseño/metodología/enfoque: Se propone un análisis cuantitativo de datos de panel con el fin de analizar el efecto del uso del teléfono móvil en zonas rurales por región del Perú durante los últimos 10 años y capturar la heterogeneidad no observable durante dicho período. De esta manera, se espera investigar el efecto del mayor uso de dicha tecnología en el Perú. Hallazgos: Los resultados obtenidos muestran que el aumento en las adquisiciones de teléfonos móviles en zonas rurales ha tenido un impacto positivo en el bienestar de los hogares. La continua innovación empresarial impulsada por las necesidades de los ciudadanos y la mayor accesibilidad a la telefonía móvil son las principales razones basadas en el contexto peruano bajo estudio. Originalidad/valor: En Perú ha habido un aumento explosivo de usuarios de teléfonos móviles en los últimos 10 años. El uso de esta tecnología puede estar llegando a los hogares rurales antes que otros servicios básicos, provocando cambios individuales y sociales y creando nuevas oportunidades de empleo e ingresos. Esto respaldaría el reciente reconocimiento del teléfono móvil como una herramienta esencial para el desarrollo, especialmente en los países subdesarrollados.
Keywords: Mobile phone; Rural households; Teléfono móvil; Wellbeing; Hogares rurales; Bienestar; Regional development; Desarrollo regional; https://purl.org/pe-repo/ocde/ford#5.02.04